Heutagogy Paradigm: Empowering Leadership Through Holistic Participatory Research in An Organization-Body - Hamdani, Hamdani; Marzuki, Marzuki; Mawardaniah, Mawardaniah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study examined the application of participatory action research to foster leadership qualities among middle-ranged members of the Muhammadiyah organization in Kota Langsa. Grounded in humanistic and constructivist principles, this approach seeks to unlock the potential traits of the organization's members. To achieve this objective, community-based participatory research (CBPR) of the participatory action research (PAR) design was employed, enabling active member participation and fostering improved leadership capabilities. The findings highlighted the significance of CBPR and the paradigm approach in validating members' experiences in leading, management, and organization. Through this study, the members have benefited themselves, their families, and the broader community for the paradigm nurture, contributing to personal and collective leadership characteristics. Therefore, the study contributes to the growing literature on empowering leadership development and showcases the efficacy of participatory research methodologies.